PREVALENSI RETINOPATI DIABETIK PADA POLIKLINIK ILMU KESEHATAN MATA SELANG SATU TAHUN - Ilery, Tiara; Sumual, Vera; Rares, Laya (Universitas Sam Ratulangi, 2014)
Abstract: Diabetic retinopathy is a disease that tends to damage retinal microvasculature as chronic progressive, related with the old hyperglycaemia and also connected with diabetes mellitus and hypertension; that can expand into certain level and can turn to serious complication. The purpose of this observation is to know about prevalence of diabetic retinopathy on Polyclinic Opthalmology BLU RSU Prof. Dr. R. D. Kandou in Manado within one year. This method of observation are retrospective descriptive which is utilize the secondary data in notes form that is taken from Department of Opthalmology BLU RSU Prof. Dr. R. D. Kandou in Manado within period June 2012 – May 2013 and October 2013. In this observation that had 498 samples, with 219 people (44%) that is positively diagnosed with diabetic retinopathy. Based from sexes it self, diabetic retinopathy occur more in female patient as much as 116 people (52,96%). However, that disease is dominated with the patient at age 45-64 year old 128 people (58,44%) that also has history of diabetes mellitus. From 219 patients retinopati diabetik, there are 200 people (91,32%) that has vision problem. As we know about the risk of this disease, we are hoping that the patient of retinopati diabetik and diabetes melitus could constantly control their blood pressure and blood sugar, as well as eyes checking to cut down future risk. Keywords: Prevalence, retinopathy, diabetic retinopathy, complication of diabetes. Abstrak: Retinopati diabetik adalah penyakit yang berpotensi merusak pembuluh darah retinal secara kronis progresif, berhubungan dengan hiperglikemia yang lama dan terkait dengan diabetes melitus juga hipertensi; dapat berkembang sampai tingkatan tertentu dan merupakan komplikasi yang serius. Tujuan penelitian adalah untuk mengetahui prevalensi retinopati diabetik pada poliklinik ilmu kesehatan mata BLU RSU Prof. Dr. R. D. Kandou Manado selang satu tahun. Metode penelitian bersifat deskriptif retrospektif dengan memanfaatkan data sekunder berupa catatan medik yang terdapat di Bagian Mata BLU RSU Prof. Dr. R. D. Kandou Manado Periode Juni 2012-Mei 2013 dan Oktober 2013. Dalam penelitian ini terdapat 498 sampel, dengan 219 orang (44%) yang terdiagnosa retinopati diabetik. Berdasarkan jenis kelamin, retinopati diabetik lebih banyak dialami pasien berjenis kelamin perempuan sebanyak 116 orang (52,96%). Sedangkan untuk rentang umur, didominasi oleh pasien dengan rentang umur 45-64 tahun sebanyak 148 orang (67,5%), dan terdapat 128 orang (58,44%) yang memiliki riwayat diabetes melitus. Dari 219 orang pasien retinopati diabetik terdapat 200 orang (91,32%) yang visusnya terganggu. Dengan melihat resiko penyakit ini, pasien retinopati diabetik dan diabetes melitus diharapkan dapat mengontrol gula darah dan tekanan darah, serta dengan rutin memeriksakan mata untuk menekan progresifitas penyakit. Kata Kunci : Prevalensi, retinopati, retinopati diabetik, komplikasi diabetes.